THE EFFECT OF INCREASED COOKING OIL PRICES ON THE INCOME AND PROFITS OF STREET VENDORS IN THE MANGLI RED LIGHT CROSSROADS JEMBER REGENCY - Suwarso (MBA - Journal of Management and Business Aplication, 2023)
This study aims to determine the increase in the price of cooking oil on the income andprofits of street vendors in the Mangli red light intersection area, Jember Regency. Thisresearch is qualitative by presenting the results of interviews in the field. The samples takenwere 129 street vendors in the Mangli red light intersection area, Jember Regency. Theresults of this study, the average income of traders during the increase in cooking oil prices isalmost 40% with smaller profits, which is decreased by around 50% than usual. This meansthat the impact caused by the increase in cooking oil prices is quite significant in affecting theincome and profits of street vendors. In addition, other influences that arise include fewercustomers every day, fewer customers buying products from street vendors, because they aremore concerned with the main product, in this case the nine basic ingredients. Withincreasing business conditions, street vendors switch professions, some even stop trading orstop waiting until the price of cooking oil recovers as before.